Improvement Of Working Facilities At The Zinc Tile Printing Station With Ergonomic Approach - Multazam, M. Rizky (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
PT. Bintang Rezeki Maju is a private company engaged in the manufacture of zinc roof tiles. The process of making zinc tile starts from printing, coloring, polishing and drying. Observations focused on the printing station because the printing station has a very important role in the zinc tile production process because it directly affects the quality of the tiles produced. The results of the study obtained a new work facility design with dimensions according to the anthropometry of the workers with specifications of chair leg height 45.14 cm, seat length 45.59 cm, seat seat width 32.51 cm, seat back height 58.26 cm, width seat backrest 41.66 cm and machine leg height 68.41 cm. With the new work facility improvement design, it can reduce operator complaints at the printing station. Anthropometric approach aims to obtain the appropriate dimensions of the operator's body for the design of work facilities. The results of the study obtained a new work facility design with dimensions according to the anthropometry of the workers with specifications of chair leg height 45.14 cm, seat length 45.59 cm, seat seat width 32.51 cm, seat back height 58.26 cm, width seat backrest is 41.66 cm and machine leg height is 68.41 cm. With the new work facility improvement design, it can reduce operator complaints at the printing station. Anthropometric approach aims to obtain the appropriate dimensions of the operator's body for the design of work facilities. The results of the study obtained a new work facility design with dimensions according to the anthropometry of the workers with specifications of chair leg height 45.14 cm, seat length 45.59 cm, seat seat width 32.51 cm, seat back height 58.26 cm, width seat backrest 41.66 cm and machine leg height 68.41 cm. With the new work facility improvement design, it can reduce operator complaints at the printing station. the height of the backrest is 58.26 cm, the width of the backrest is 41.66 cm and the height of the machine leg is 68.41 cm. With the new work facility improvement design, it can reduce operator complaints at the printing station. the height of the backrest is 58.26 cm, the width of the backrest is 41.66 cm and the height of the machine leg is 68.41 cm. With the new work facility improvement design, it can reduce operator complaints at the printing station.